A Practical Guide to Minimal Surgery for Retinal Detachment : Volume II. (Georg Thieme Verlag, 2000)
Dr. Kreissig has spent a lifetime refining and teaching the minimalized approach to repairing retinal detachments. Get the benefit of her experience in an easily ...